Trading off nutrition and education? A panel data analysis of the dissimilar welfare effects of organic and fairtrade standards - Eva-Marie Meemken; David J. Spielman; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
Millions of smallholder farmers in developing countries participate in different types of sustainability standards. A growing body of literature has analyzed the welfare effects of such participation, with mixed results. Yet, there are important knowledge gaps. First, most existing studies look at the effects of one standard in one country. When comparing between studies it is not clear whether dissimilar outcomes are driven by differences in standards or local conditions. Second, most studies use cross-section, observational data, so that selectivity issues remain a challenge. Third, the existing work has primarily analyzed effects in terms of purely economic indicators, such as income, ignoring other dimensions of household welfare. We address these shortcomings using panel data from small-scale coffee producers in Uganda and comparing the effects of two of the most popular sustainability standards, namely Organic and Fairtrade. Welfare effects are analyzed in terms of household expenditures, child education, and nutrition. Results show that Organic and Fairtrade both have positive effects on total consumption expenditures. However, notable differences are observed in terms of the other outcomes. Organic contributes to improved nutrition but has no effect on education. For Fairtrade it is exactly the other way around. We explore the mechanisms behind these differences.
Keywords: Q01; Q12; Q13; Q18; 330; certification; education; food standards; nutrition; panel data; welfare